Pengaruh Penggunaan Metode Diskusi Kelompok dan Metode Ceramah Terhadap Hasil Belajar Pendidikan Kewarganegaraan Siswa Kelas VII MTs Miftahul Mubtadiin - Rifi Hamdani; Sunardjo; Dian Eka Indriani (Penerbit STKIP PGRI Bangkalan, 2019)
Civics Education (PKn) is a subject that aims to educate students to foster morale and to make good citizens, which is expected to be realized in daily life, both within the school environment and outside the school environment. Civics education (PKn) was originally supposed to be able to shape the activeness, creativity, and intelligent thinking of students in solving any existing problem by way of consensus agreement in accordance with the IV points of Pancasila precepts, namely